Seismic performance of railway rounded rectangular hollow tall piers using the shaking table test. (1st October 2020) - Qi, Qiming; Shao, Changjiang; Wei, Wang; Xiao, Zhenghao; He, Junming
Highlights: Shaking table tests of three 1/6-scale rounded rectangular hollow tall piers were conducted. A second plastic hinge appeared at the middle region of piers due to higher-mode effects. The damage behaviors were found to be different with those of the semistatic specimens sharing the same section. Abstract: The seismic performance of rounded rectangular hollow tall piers, applied popularly in railway bridges in high-intensity areas in China, has rarely been investigated till now. The current seismic design approaches mostly stem from short-to-medium solid columns whose seismic behavior is different from those of hollow members. According to cyclic tests in publications, there are also obvious differences in the seismic performance between the rounded rectangular hollow piers and the common hollow ones. To clarify the differences among them and update the existing design approach, the damage modes and dynamic responses of rounded rectangular hollow columns under different-level earthquakes should be studied comprehensively. Therefore, three 1/6-scale models from a 40 m prototype pier were tested using a 10.1 m × 8.1 m 6DOFs shaking table. The experimental outcomes were analyzed and compared with those previous semistatic tests. The results showed that the three specimens underwent flexural damage with horizontal cracks distributing along the whole body. Moreover, a second plastic hinge region, evidenced by the denser flexural cracks around the middle part, appeared in addition to the lengthened plastic hinge close to the pier footing. These findings are mainly attributed to the combined influence of the variable hollow section and higher-order effects, which differs greatly from the damage behaviors of specimens under cyclic loads. As expected, the increased stirrup ratio produced great improvement in the seismic performance of rounded rectangular hollow tall piers (DB1 and DB2), while fewer stirrups corresponded to a decrease in ductility (DB3).